Postoperative anaemia and patient-centred outcomes after major abdominal surgery: a retrospective cohort study. (September 2022) - Myles, Paul S.; Richards, Toby; Klein, Andrew; Wood, Erica M.; Wallace, Sophie; Shulman, Mark A.; Martin, Catherine; Bellomo, Rinaldo; Corcoran, Tomás B.; Peyton, Philip J.; Story, David A.; Leslie, Kate; et al.
Abstract: Background: Compared with anaemia before surgery, the underlying pathogenesis and implications of postoperative anaemia are largely unknown. Methods: This retrospective cohort study analysed prospective data obtained from 2983 adult patients across 47 centres enrolled in a clinical trial evaluating restrictive and liberal intravenous fluids. The primary endpoint was persistent disability or death up to 90 days after surgery. Secondary endpoints included major septic complications, hospital stay, and patient quality of recovery using a 15-item quality of recovery (QoR-15) score, hospital re-admissions, and disability-free survival up to 12 months after surgery. Anaemia and disability were defined according to the WHO definitions. Multivariable regression was used to adjust for baseline risk and surgery. Results: A total of 2983 patients met inclusion criteria for this study, of which 78.5% (95% confidence interval [CI], 76.7–80.1%) had postoperative anaemia. Patients with postoperative anaemia had a higher adjusted risk of death or disability up to 90 days after surgery when compared with those without anaemia: 18.2% vs 9.2% (risk ratio [RR]=1.51; 95% CI, 1.10–2.07, P =0.011); lower QoR-15 scores on Day 3 and Day 30, 105 (95% CI, 87–119) vs 114 (95% CI, 99–128; P <0.001), and 130 (95% CI, 112–140) vs 139 (95% CI, 121–144; P <0.011), respectively; higher adjusted risk of a composite of mortality/septic complications, 2.01 (95% CI, 1.55–42.67; P <0.001); unplanned admission to ICU (RR=2.65; 95% CI, 1.65–4.23; P <0.001); and longer median (inter-quartile range [IQR]) hospital stays, 6.6 (4.4–12.4) vs 3.7 (2.5–6.5) days ( P <0.001). Conclusions: Postoperative anaemia is common and is independently associated with poor outcomes after surgery. Optimal prevention and treatment strategies need to be investigated. Clinical trial registration: NCT04978285 (ClinicalTrials.gov ).